On Integral Operators with Homogeneous Kernels in Morrey Spaces - Avsyankin, Oleg (Eurasian Mathematical Journal, 2021)
We consider integral operators with homogeneous kernels in Morrey spaces. For such operators we obtain sufficient conditions of their boundedness. Moreover, for an operator, which is the sum of the identity operator and an operator with a homogeneous kernel, we prove the invertibility criterion.